Efficacy of scissor‐type knives for endoscopic mucosal dissection of superficial gastrointestinal neoplasms. Issue 1 (14th June 2019) - Yoshida, Naohisa; Dohi, Osamu; Inoue, Ken; Yasuda, Ritsu; Ishida, Tsugitaka; Hirose, Ryohei; Naito, Yuji; Ogiso, Kiyoshi; Murakami, Takaaki; Morinaga, Yukiko; Kishimoto, Mitsuo; Inada, Yutaka; et al.
Abstract : Endoscopic submucosal dissection (ESD) for superficial gastrointestinal neoplasms has become widespread. However, certain aspects of the procedure remain difficult to manage, such as intraoperative bleeding and perforation. There are two kinds of scissor‐type knife: the Clutch Cutter (Fujifilm Co., Tokyo, Japan) and the SB knife (Sumitomo Bakelite Co., Tokyo, Japan). These knives have different features from other types of ESD knives and enable the performance of all ESD procedures, including mucosal incision, submucosal dissection, and hemostasis. The standard approach with scissor‐type knives involves first grabbing the tissue and then incising or dissecting it. Theoretically, perforation as a result of unintentional movement should never happen with scissor‐type knives compared to needle‐ or blade‐type knives, which may induce perforation through unintentional movement. Moreover, the rates of severe bleeding and self‐completion of ESD with scissor‐type knives by non‐experts were reported to be significantly better than for other knives. Thus, scissor‐type knives can resolve these problems and help to further standardize ESD globally. In this review, we summarize reports on the efficacy of such scissor‐type knives for ESD of gastrointestinal tumors. We also present the pocket‐creation method and the application of traction devices, such as dental floss and S‐O clips (Zeon Medical Co., Tokyo, Japan) for improving the performance of ESD with a Clutch Cutter.